2000
DOI: 10.1046/j.1365-2133.2000.03891.x
|View full text |Cite
|
Sign up to set email alerts
|

A clinical study of 23 cases of female anogenital carcinoma

Abstract: An underlying skin disorder prior to the development of their carcinoma was found in 22 of 23 patients with vulval SCC and is therefore an important risk factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
4

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(41 citation statements)
references
References 29 publications
0
37
0
4
Order By: Relevance
“…In other forms, SCC (Lewis & Harrington 1994) and SCC in situ (Franck & Young 1995) have been reported. Studies of patients with established vulval malignancy have demonstrated associated lichen planus (Zaki et al 1997, Derrick et al 2000 in the surrounding epithelium.…”
Section: Differential Diagnosismentioning
confidence: 99%
“…In other forms, SCC (Lewis & Harrington 1994) and SCC in situ (Franck & Young 1995) have been reported. Studies of patients with established vulval malignancy have demonstrated associated lichen planus (Zaki et al 1997, Derrick et al 2000 in the surrounding epithelium.…”
Section: Differential Diagnosismentioning
confidence: 99%
“…12 There are at least 12 reports of SCC and vulval LP, but no estimates of SCC risk. [29][30][31][32][33][34][35] A much larger multicenter, longitudinal study will be necessary to evaluate accurately the characteristics of those who develop SCCs. It is unknown whether early treatment of LP lessens the risk of malignancy.…”
Section: Commentmentioning
confidence: 99%
“…Das Tumorwachstum beginnt in der Regel nicht de novo; es entsteht meist auf vorgeschädigter Haut, wie beispielsweise bei Kondylombefall [1,4,11,13,14,20], bei Lichen ruber planus [5], Acne inversa [7,12,15,19], Morbus Crohn [10,16] und Lichen sclerosus et atrophicans [3,17,18]. Eine Immunsuppression begünstigt die Tumorentstehung [6,9].…”
Section: äTiopathogeneseunclassified